Ralstonia solanacearum promotes pathogenicity by utilizing l‐glutamic acid from host plants. (29th June 2020) - Shen, Fangfang; Yin, Wenfang; Song, Shihao; Zhang, Zhihan; Ye, Peiyi; Zhang, Yong; Zhou, Jianuan; He, Fei; Li, Peng; Deng, Yinyue
Abstract: Ralstonia solanacearum is an important bacterial pathogen that can infect a broad range of plants worldwide. A previous study showed that R. solanacearum could respond to exogenous organic acids or amino acids to modulate cell motility. However, it was unclear whether R. solanacearum uses these compounds to control infection. In this study, we found that R. solanacearum GMI1000 uses host plant metabolites to enhance the biosynthesis of virulence factors. We demonstrated that l ‐glutamic acid from host plants is the key active component associated with increased extracellular polysaccharide production, cellulase activity, swimming motility, and biofilm formation in R. solanacearum GMI1000. In addition, l ‐glutamic acid also promoted colonization of R. solanacearum cells in the roots and stems of tomato plants and accelerated disease incidence. Furthermore, genetic screening and biochemical analysis suggested that RS01577, a hybrid sensor histidine kinase/response regulator, is involved in l ‐glutamic acid signalling in R. solanacearum . Mutations in RS01577 and exogenous addition of l ‐glutamic acid to the GMI1000 wild‐type strain had overlapping effects on both the transcriptome and biological functions of R. solanacearum, including on motility, biofilm formation, and virulence. Thus, our results have established a new interaction mechanism between R. solanacearum and host plants that highlights the complexity of the virulence regulation mechanism and may provide new insight into disease control. Abstract : Ralstonia solanacearum perceives l‐ glutamic acid from host plants to enhance extracellular polysaccharide production, cellulase activity, swimming motility, biofilm formation, and virulence.